2024
DOI: 10.1111/obr.13691
|View full text |Cite
|
Sign up to set email alerts
|

MHO or MUO? White adipose tissue remodeling

Jing Yi Zhao,
Li Juan Zhou,
Kai Le Ma
et al.

Abstract: SummaryIn this review, we delve into the intricate relationship between white adipose tissue (WAT) remodeling and metabolic aspects in obesity, with a specific focus on individuals with metabolically healthy obesity (MHO) and metabolically unhealthy obesity (MUO). WAT is a highly heterogeneous, plastic, and dynamically secreting endocrine and immune organ. WAT remodeling plays a crucial role in metabolic health, involving expansion mode, microenvironment, phenotype, and distribution. In individuals with MHO, W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 382 publications
0
1
0
Order By: Relevance
“… 22 Adipose tissue metabolism disorders have effects on glycolipid metabolism, cytokine and adipokine secretion. 23 Disorders of glycolipid metabolism and abnormal secretion of lipokines induce systemic inflammation, suggesting that inflammatory cytokines of WAT may be an important regulator for metabolic diseases. It is reported that inflammatory cytokines exacerbate diabetes mellitus by disrupting pancreatic β‐cell survival.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Adipose tissue metabolism disorders have effects on glycolipid metabolism, cytokine and adipokine secretion. 23 Disorders of glycolipid metabolism and abnormal secretion of lipokines induce systemic inflammation, suggesting that inflammatory cytokines of WAT may be an important regulator for metabolic diseases. It is reported that inflammatory cytokines exacerbate diabetes mellitus by disrupting pancreatic β‐cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Adipocyte size varies according to several factors, including sex and fat depot (lower in vWAT than in sWAT in women, but not in It is worth noting that the adipogenic capacity of sWAT is not only limited but also extremely variable among individuals, as shown by the existence of persons with obesity either with or without insulin resistance and components of the metabolic syndrome, including impaired glucose regulation, atherogenic dyslipidemia, and hypertension, despite the same body mass index (BMI). In addition to these two obese phenotypes, which are called metabolic unhealthy obese (MUO) and metabolic healthy obese (MHO), respectively [17,18], there are also lean phenotypes characterized by the presence or absence of metabolic derangement, i.e., the metabolic unhealthy normal weight (MUNW), also called metabolically obese normal weight [MONW], and the metabolic healthy normal weight (MHNW), respectively [19]. This indicates that it is not just a matter of absolute quantity of fat and shifts the focus on sWAT dysfunction and remodeling of fat depots, which is dependent on the individual capacity to expand and accommodate the surplus of energy [20].…”
Section: Adipocyte Size As a Marker Of White Adipose Tissue Dysfunctionmentioning
confidence: 99%